Biology of microorganisms - Brock, Thomas D. (Prentice Hall, 1991)
This text emphasizes the principles of microbiology, presenting both the general and molecular aspects of microbiology. The sixth edition expands material on microbial diseases to hrlp instructors taking a medical microbiological approach to the material. It includes revision study questions which are designed to encourage students to synthesize information and draw conclusions.